NILAI-NILAI PENDIDIKAN SOSIAL DALAM BUDAYA BEBUBUS BATU - SOPIAN ANSORI; Sunandar azma’uL Hadi (Jurnal Budaya Nusantara, 2023)
This study aims to describe the values ​​of social education contained in the bebubus batu ritual in Batu Pandang, Sapit Village, Suela District, East Lombok. The bebubus batu ritual is one of the cultural rituals carried out by the community at least twice a year in the hope that the residents' agriculture will be blessed by Allah SWT. This ritual is an ancestral heritage that has been passed down from generation to generation. The current generation has managed to preserve it well, so that people can reap the various noble values ​​contained in it. Data collection methods used are observation, interviews and documentation. Data were analyzed using descriptive analytic method. The values ​​of social education contained in the stone bebubus ritual include the value of mutual cooperation, the value of deliberation, the value of tawadhu', the value of respecting nature, and the value of appreciating food. Keywords: Social Values, Batu Pandang, Bebubus batu